Genome‐wide association study reveals candidate genes associated with body measurement traits in Chinese Wagyu beef cattle. (10th June 2019) - An, B.; Xia, J.; Chang, T.; Wang, X.; Xu, L.; Zhang, L.; Gao, X.; Chen, Y.; Li, J.; Gao, H.
Summary: We performed a genome‐wide association study to identify candidate genes for body measurement traits in 463 Wagyu beef cattle typed with the Illumina Bovine HD 770K SNP array. At the genome‐wide level, we detected 18, five and one SNPs associated with hip height, body height and body length respectively. In total, these SNPs are within or near 11 genes, six of which ( PENK, XKR4, IMPAD1, PLAG1, CCND2 and SNTG1 ) have been reported previously and five of which ( CSMD3, LAP3, SYN3, FAM19A5 and TIMP3 ) are novel candidate genes that we found to be associated with body measurement traits. Further exploration of these candidate genes will facilitate genetic improvement in Chinese Wagyu beef cattle.